Computational Fluid Dynamics Characterization of High‐Capacity Structured Packing. Issue 9 (12th June 2020) - Manh, Tran Dinh; Nam, Nguyen Dang; Babazadeh, Houman; Moradi, Rasoul
Abstract: The novel wire gauze structured packing, PACK‐860, was characterized by means of numerical methods. The main features of PACK‐860 such as height equivalent to a theoretical plate ( HETP ) and dry/wet pressure drop were evaluated. The flow structure in this packing was described by numerical simulation. To estimate the amount of HETP and dry/wet pressure drop, three‐dimensional computational fluid dynamics (3D CFD) modeling with the Eulerian‐Eulerian multiphase approach was applied. The average relative errors between the results obtained from CFD simulation and experimental findings for mass transfer efficiency and wet and dry pressure drop were assessed. Numerical observations were found to agree well with the empirical results, proving the reliability of CFD simulations for modeling separation processes. Abstract : A novel wire gauze structured packing was characterized by numerical methods and the key hydrodynamic features of this packing including dry/wet pressure drop were evaluated for an air‐water system. The amount of height equivalent to a theoretical plate and the pressure drop were determined by three‐dimensional computational fluid dynamics simulation with Eulerian‐Eulerian multiphase scheme.